1963
DOI: 10.1002/andp.19634670308
|View full text |Cite
|
Sign up to set email alerts
|

Theorie des Quanten‐Plasmas

Abstract: InhaltsiibersichtEs wird die quantenstatistische Zustandssumme eines N-Teilchensystems im Falle weitreichender zwischenmolekularer Wechselwirkungen berechnet. Das Verfahren ist anwendbar, wenn die Potentiale Fourier-Transformierte besitzen. Durch Einfiihrung effektiver Potentiale, die von der Temperatur und dem P l a n c kschen Wirkungsquantum abhlingen, wird es moglich, bekannte klassische Gleichungen heranzuziehen und Formeln fur die freie Energie und die radiale Verteilungsfunktion aufzustellen. I m Falle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 9 publications
3
131
0
Order By: Relevance
“…In the high-temperature limit, ρ ab factorizes into a kinetic (ρ 0 ) and an interaction term (ρ ab U ), ρ ab ≈ ρ 0 ρ ab U , because it can be shown that [40,41] …”
Section: High-temperature Asymptotics Of the Density Matrix In Tmentioning
confidence: 99%
“…In the high-temperature limit, ρ ab factorizes into a kinetic (ρ 0 ) and an interaction term (ρ ab U ), ρ ab ≈ ρ 0 ρ ab U , because it can be shown that [40,41] …”
Section: High-temperature Asymptotics Of the Density Matrix In Tmentioning
confidence: 99%
“…Here U eff is the effective pair action, 26,28 introduced in a way that at large distances and (or) high temperatures it reduces to β(e 2 / |r hh | + E (n) e (r hh )). Substituted in Eq.…”
mentioning
confidence: 99%
“…For large distances r > δ the potential becomes Coulomb, while for r < δ the Coulomb singularity is removed and u ei (0) = 1/δ. By this the short range effects based on the uncertainty principle are included [31][32][33]. For a classical description of a plasma the electron degeneracy parameter Θ e , i.e., the ratio of the thermal energy and the Fermi energy must fulfill Θ e = k B T /E F > 1.…”
Section: MD Simulationsmentioning
confidence: 99%